2019
DOI: 10.1093/mnras/stz265
|View full text |Cite
|
Sign up to set email alerts
|

The 3D shape of Type IIb SN 2011hs

Abstract: We observed seven epochs of spectropolarimetry in optical wavelengths for the Type IIb SN 2011hs, ranging from −3 to +40 days with respect to V -band maximum. A high degree of interstellar polarization was detected (up to ∼3 percent), with a peak lying blueward of 4500Å. Similar behaviours have been seen in some Type Ia SNe, but had never been observed in a Type IIb. We find that it is most likely the result of a relative enhancement of small silicate grains in the vicinity of the SN. Significant intrinsic con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…The presence of loops provides evidence for departures from a simple bi-axial (e.g. ellipsoidal; see Stevance et al 2019) configuration of the ejecta and is a natural consequence of mixing in a deflagration phase of burning, which is common to our model and the PDD models invoked by Stritzinger et al (2015).…”
Section: Signatures From the Explosionsupporting
confidence: 70%
“…The presence of loops provides evidence for departures from a simple bi-axial (e.g. ellipsoidal; see Stevance et al 2019) configuration of the ejecta and is a natural consequence of mixing in a deflagration phase of burning, which is common to our model and the PDD models invoked by Stritzinger et al (2015).…”
Section: Signatures From the Explosionsupporting
confidence: 70%
“…The optical and NIR spectra of SN 2020oi span days 2-67, and those of SN 2020bvc span days 1-73. The rest wavelengths of the lines (note that we use angstroms in STP air for the optical spectra and microns in vacuum for the NIR spectra) are from the SN spectral models by Dessart et al (2012) and synthesized spectra using SYNAPPS (Thomas et al 2011), other observed spectra of SNe Ic (Hunter et al 2009;Gerardy et al 2002;Drout et al 2016;Stevance et al 2017Stevance et al , 2019, or SNe Ib (Ergon et al 2014;Jencson et al 2017). The spectra of both SNe are dominated by atomic lines, in absorption or in emission, and sometimes simultaneously in the form of P Cygni profiles.…”
Section: Light Curves and Explosion Properties Of Sn 2020bvcmentioning
confidence: 99%
“…Since this is the first late-phase spectropolarimetric data for SLSNe-I, it is too early to draw the firm conclusions about the general ejecta geometry of SLSNe-I. Also, unfortunately, there are not many polarization data for normal stripped-envelope SNe (e.g., Tanaka et al 2012), in particular those with a good time series except for a few cases (Mauerhan et al 2015;Stevance et al 2017Stevance et al , 2019. Therefore, it is not easy to readily compare the geometry between normal stripped-envelope SNe and SLSNe-I in terms of polarization.…”
Section: Discussionmentioning
confidence: 96%